What Is the Economic Burden of Subsidized HIV/AIDS Treatment Services on Patients in Nigeria and Is This Burden Catastrophic to Households? - Enyi Etiaba; Obinna Onwujekwe; Kwasi Torpey; Benjamin Uzochukwu; Robert Chiegil (PLoS ONE, 2016)
A gap in knowledge exists regarding the economic burden on households of subsidized anti-retroviral treatment (ART) programs in Nigeria. This is because patients also incur non-ART drug costs, which may constrain the delivery and utilisation of subsidized services.An exit survey of adults (18+years) attending health facilities for HIV/AIDS treatment was conducted in three states in Nigeria (Adamawa, Akwa Ibom and Anambra). In the states, ART was fully subsidized but there were different payment modalities for other costs of treatment. Data was collected and analysed for direct and indirect costs of treatment of HIV/AIDS and co-morbidities' during out-and in-patient visits. The levels of catastrophic health expenditure (CHE) were computed and disaggregated by state, socio-economic status (SES) and urban-rural location of the respondents. Catastrophic Health Expenditure (CHE) in this study measures the number of respondents whose monthly ART-related household expenditure (for in-patient and out-patient visits) as a proportion of monthly non-food expenditure was greater than 40% and 10% respectively.The average out-patient and in-patient direct costs were $5.49 and $122.10 respectively. Transportation cost was the highest non-medical cost and it was higher than most medical costs. The presence of co-morbidities contributed to household costs. All the costs were catastrophic to households at 10% and 40% thresholds in the three states, to varying degrees. The poorest SES quintile had the highest incidence of CHE for out-patient costs (p<0.0001). Rural dwellers incurred more CHE for all categories of costs compared to urban dwellers, but the costs were statistically significant for only outpatient costs.ART subsidization is not enough to eliminate economic burden of treatment on HIV patients. Service decentralization to reduce travel costs, and subsidy on other components of HIV treatment services should be introduced to eliminate the persisting inequitable and high cost burden of ART services. Full inclusion of ART services within the benefit package of the National Health Insurance Scheme should be considered.